Inactivation of SARS‐CoV‐2 infectivity in platelet concentrates or plasma following treatment with ultraviolet C light or with methylene blue combined with visible light. Issue 2 (8th January 2023) - Hobson‐Peters, Jody; Amarilla, Alberto A.; Rustanti, Lina; Marks, Denese C.; Roulis, Eileen; Khromykh, Alexander A.; Modhiran, Naphak; Watterson, Daniel; Reichenberg, Stefan; Tolksdorf, Frank; Sumian, Chryslain; Seltsam, Axel; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is unlikely to be a major transfusion‐transmitted pathogen; however, convalescent plasma is a treatment option used in some regions. The risk of transfusion‐transmitted infections can be minimized by implementing Pathogen Inactivation (PI), such as THERAFLEX MB‐plasma and THERAFLEX UV‐Platelets systems. Here we examined the capability of these PI systems to inactivate SARS‐CoV‐2. Study Design and Methods: SARS‐CoV‐2 spiked plasma units were treated using the THERAFLEX MB‐Plasma system in the presence of methylene blue (~0.8 μmol/L; visible light doses: 20, 40, 60, and 120 [standard] J/cm 2 ). SARS‐CoV‐2 spiked platelet concentrates (PCs) were treated using the THERAFLEX UV‐platelets system (UVC doses: 0.05, 0.10, 0.15, and 0.20 [standard] J/cm 2 ). Samples were taken prior to the first and after each illumination dose, and viral infectivity was assessed using an immunoplaque assay. Results: Treatment of spiked plasma with the THERAFLEX MB‐Plasma system resulted in an average ≥5.03 log10 reduction in SARS‐CoV‐2 infectivity at one third (40 J/cm 2 ) of the standard visible light dose. For the platelet concentrates (PCs), treatment with the THERAFLEX UV‐Platelets system resulted in an average ≥5.18 log10 reduction in SARS‐CoV‐2 infectivity at the standard UVC dose (0.2 J/cm 2 ). Conclusions: SARS‐CoV‐2 infectivity was reduced in plasma and platelets following treatment with the THERAFLEX MB‐Plasma and THERAFLEX UV‐Platelets systems, to the limit of detection, respectively. These PI technologies could therefore be an effective option to reduce the risk of transfusion‐transmitted emerging pathogens.